Correlation of inflammatory markers and NFATC4 gene expression among subjects with prediabetes. - Rajan, Aswathi; L, Karpagavel; S, Vidya; K S, Sheena; M D, Harilal; S, Deepthi; K, Manjusha; Raveendran, Rachana; P V, Ambili; T M, Midhun; T, Swathi; D, Dinesh Roy (Journal of Cardiovascular & Thoracic Research, 2024)
Introduction: Prediabetes, characterized by mildly elevated blood sugar levels, significantly increases the risk of developing type 2 diabetes and cardiovascular disease. The condition is linked to higher levels of IL-18, TNF-α, and IL-6, indicating inflammation that may drive type 2 Diabetes Mellitus (T2DM). Despite the known role of inflammation in glucose homeostasis, the involvement of the Nuclear Factor of Activated T Cells 4 (NFATC4) gene in prediabetes remains underexplored. This case-control study aims to investigate the association between physiological, demographic, anthropometric, lifestyle factors, inflammatory markers and NFATC4 gene expression, in the context of prediabetes. Methods: The study involved 300 participants aged 20 to 50, with 150 diagnosed with prediabetes and 150 healthy controls. After obtaining informed consent fasting venous blood samples were collected for comprehensive assessments, including biochemical, endocrinological and immunological analyses. Specifically, NFATC4 gene expression and inflammatory markers were measured. Results: The findings revealed significantly elevated levels of IL-18, TNF-α, IL-6, and NFATC4 expression in prediabetic individuals compared to controls. Notably, strong positive correlations were observed between NFATC4 expression and the inflammatory markers. Receiver operating characteristic (ROC) curve analysis identified IL-18 and NFATC4 as the most promising biomarkers for predicting prediabetes, followed by TNF-α and IL-6. Multivariate regression analysis further identified socioeconomic status (SES), IL-18, NFATC4, TSH, triglycerides, and HDL as independent predictors of prediabetes. Conclusion: These results highlight the key role of inflammation and NFATC4 in prediabetes, stressing the need for strategies to prevent progression to type 2 diabetes and cardiovascular issues.